РАДИОСТРУКТУРА ИСТОЧНИКА 1803÷784 - Чуприков A. А. (Одеські астрономічні публікації, 2011)
Results of processing of data of ground-space VLBI experiment titled V053 are presented. These observations were made in 1997 October with 10 antennas of American interferometer VLBA and with Japan space telescope VSOP (VLBI Space Orbit Program). Data were transferred from the NRAO archive and processed with the software “Astro Space Locator” (ASL for Windows). The main result is radio image of the known quasar 1803+784. Properties of the ground-space VLBI data processing are discussed.